저울 모델에 기반한 일차방정식 풀이 교수가 수학학습장애 중학생의 일차방정식 연산 능력에 미치는 효과 - 김애화(Kim Ae Hwa); 백지은(Baek Ji Eun) (특수교육논총, 2022)
연구목적: 본 연구에서는 저울 모델에 기반한 일차방정식 풀이 교수가 수학학습장애 중학생의 일차방정식 연산 능력에 미치는 효과를 살펴보았다. 연구방법: 연구 대상은 경기도 A 지역아동센터에 소속된 수학학습장애 중학생 3명이었다. 연구 설계 방법으로는 중다 간헐 기초선 설계를 적용하였다. 본 연구에서는 저울 모델에 기반한 일차방정식 풀이를 구체물-반구체물-추상물 단계에 따라 명시적 교수를 통해 교수하였다. 연구결과: 주요 연구 결과는 다음과 같다. 첫째, 저울 모델에 기반한 일차방정식 풀이 교수는 수학학습장애 중학생의 일차방정식 연산 능력을 향상시키는 것으로 나타났다. 둘째, 교수의 효과는 교수가 끝난 뒤에도 유지되었다. 결론: 저울 모델에 기반한 일차방정식 풀이 교수는 수학학습장애 중학생의 일차방정식 연산 능력을 향상시키기 위한 효과적인 교수로 나타났으며, 끝으로 연구의 결론 및 논의점을 제시하였다. Purpose: The purpose of this study was to analyze the effect of the interventions of linear equation solving based on the balance model on the ability of middle school students with mathematical learning disabilities to calculate linear equations. Method: The subjects of the study were three middle school students with math learning disabilities belonging to the A Regional Children's Center in Gyeonggi-do. As a research design method, multi probe design was applied. In this study, the equation solution based on the balance model was taught through an explicit instruction according to the concrete-semiconcrete-abstract stage. Result: The main research results are as follows. First, it was found that the linear equation solving interventions based on the balance model improves the linear equation calculation ability of middle school students with math learning disabilities. Second, the effect of the interventions was maintained even after the interventions were over. Conclusion: The conclusions and discussion of the study were presented. The linear equation solving interventions based on the balance model appeared as an effective intervention to improve the linear equation computing ability of middle school students with math learning disabilities, and finally, the conclusions and discussions of the study were presented. KCI Citation Count: 1